2022
DOI: 10.2166/aqua.2022.034
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall data used for rainwater harvesting systems: a bibliometric and systematic literature review

Abstract: The demand for water has led to an increase in scarcity events in several urban regions. In an urban context, water consumption in buildings plays an important role and rainwater harvesting is one of the ways that consumption can be reduced. One of the input variables for the dimensioning of rainwater tanks is the pluviometric regime's characteristics in the region where the rainwater harvesting system (RWHS) is to be installed. In this study, a bibliometric and systematic literature review was carried out on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 89 publications
0
2
0
2
Order By: Relevance
“…Duka et al [43] indicated that there is no single best representation of a storm, with the result that a given distribution will be better in some cases and worse in others. The possibility of using different rainfall data was also noted by Fioramonte et al [44]. Considering this, this study was conducted using the same rainfall model as in the previous stage of the analysis [35].…”
Section: Rainfall Datamentioning
confidence: 94%
“…Duka et al [43] indicated that there is no single best representation of a storm, with the result that a given distribution will be better in some cases and worse in others. The possibility of using different rainfall data was also noted by Fioramonte et al [44]. Considering this, this study was conducted using the same rainfall model as in the previous stage of the analysis [35].…”
Section: Rainfall Datamentioning
confidence: 94%
“…Penyimpanan air hujan (Rainwater Harvesting/RWH) menjadi teknologi air paling dekat dengan masyarakat Indonesia, melibatkan pengumpulan, penyimpanan, dan pelestarian hujan untuk penggunaan pertanian dan lainnya, berfungsi sebagai irigasi tambahan selama kekurangan air (Fioramonte et al, 2022). Sistem ini umum digunakan negara-negara seperti Jepang, Singapura, Amerika Serikat, dan lainnya (Custódio & Ghisi, 2023).…”
Section: Teknologi Dan Praktik Pertanian Hemat Airunclassified
“…A bibliometric analysis was used as a tool. Its application allows us to recognize trends in research, assess their interdisciplinarity, and measure the strength of influence in the world of science [44,45]. This analysis has not yet been used to assess the possibilities of heat recovery from wastewater at all points of the system.…”
Section: Introductionmentioning
confidence: 99%